What proverb understanding reveals about how people think. [article]. - Gibbs, Raymond W.
The ability to understand proverbial sayings, such as a rolling stone gathers no moss has been of great interest to researchers in many areas of psychology. Most psychologists assume that understanding the figurative meanings of proverbs requires various kinds of higher order cognitive abilities. The authors review the findings on proverb interpretation to examine the question of what proverb use and understanding reveals about the ways normal and dysfunctional individuals think. The widely held idea that failure to provide a figurative interpretation of a proverb necessarily reflects a deficit in specialized abstract thinking is rejected. Moreover, the ability to correctly explain what a proverb means does not necessarily imply that an individual can think abstractly. Various empirical evidence, nonetheless, suggests that the ability to understand many proverbs reveals the presence of metaphorical schemes that are ubiquitous in everyday thought. --(from the author).